Chemical Biology of Nucleic Acids Fundamentals and Clinical Applications - Erdmann, Volker A.; Markiewicz, Wojciech T.; Barciszewski, Jan (RNA Technologies,, 2014)
This volume contains 29 engrossing chapters contributed by worldwide, leading research groups in the field of chemical biology. Topics include pre-biology; the establishment of the genetic code; isomerization of RNA; damage of nucleobases in RNA; the dynamic structure of nucleic acids and their analogs in DNA replication, extra- and intra-cellular transport; molecular crowding by the use of ionic liquids; new technologies enabling the modification of gene expression via editing of therapeutic genes; the use of riboswitches; the modification of mRNA cap regions; new approaches to detect appropriately modified RNAs with EPR spectroscopy and the use of parallel and high-throughput techniques for the analysis of the structure and new functions of nucleic acids. This volume discusses how chemistry can add new frontiers to the field of nucleic acids in molecular medicine, biotechnology and nanotechnology and is not only an invaluable source of information to chemists, biochemists and life scientists but will also stimulate future research.